Pediatric cardiac surgery - Mavroudis, Constantine; Backer, Carl L. (Wiley-Blackwell, 2023)
"This is the 5th edition of Pediatric Cardiac Surgery. The first edition was published by Arciniegas in 1985 and was followed by the second edition in 1994, the third edition in 2003, and the fourth edition in 2013 by the present editors. Timely updates are important for any textbook since scientific intellectual curiosity, sentinel discoveries, and technological improvements have progressed at lightning speed. Even Cardiac Embryology, a field which was thought to be constant and thoroughly studied has emerged with the new findings of a second heart field, detailed results of syndromic genomes, and the promise of new paradigms and ontologies. Our readership from around the world has included numerous colleagues comprised of surgeons, cardiologists, intensivists, anesthesiologists, residents, students, perfusionists, and nurses. They have found the book to be well organized, easy to read, and to the point. We have preserved this format for the 5th Edition and added several chapters that have mirrored the directions and practice of pediatric and congenital heart surgery in the 21st century"--
Includes bibliographical references and index
Keywords: Cardiac Surgical Procedures; Heart Defects, Congenital / surgery; Infant; Child